Pregunta
Consider the following integral. Find a change of variables to rewrite the integrand as \( u^{2} d u \). \( \left.x^{2}-3\right)^{2}(2 x) d x \) \( u=\square \) \( d u=\square \) Evaluate the given integral. (Remember the constant of integration.) du R
Ask by Franklin Brooks. in the United States
Feb 02,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
Let \( u = x^{2} - 3 \), then \( du = 2x \, dx \). The integral becomes \( \int u^{2} \, du = \frac{u^{3}}{3} + C = \frac{(x^{2} - 3)^{3}}{3} + C \).
Solución
To evaluate the integral
\[
\int \left(x^{2} - 3\right)^{2} (2x) \, dx,
\]
we can use the method of **substitution** (also known as **change of variables**). Here's a step-by-step guide:
### Step 1: Choose a Substitution
Let’s choose:
\[
u = x^{2} - 3
\]
This substitution simplifies the expression inside the integral.
### Step 2: Differentiate to Find \( du \)
Differentiate both sides with respect to \( x \):
\[
\frac{du}{dx} = 2x \quad \Rightarrow \quad du = 2x \, dx
\]
Notice that \( 2x \, dx \) is present in the original integral, which matches \( du \).
### Step 3: Rewrite the Integral in Terms of \( u \) and \( du \)
Substitute \( u \) and \( du \) into the integral:
\[
\int \left(x^{2} - 3\right)^{2} (2x) \, dx = \int u^{2} \, du
\]
### Step 4: Integrate with Respect to \( u \)
Now, integrate \( u^{2} \) with respect to \( u \):
\[
\int u^{2} \, du = \frac{u^{3}}{3} + C
\]
where \( C \) is the constant of integration.
### Step 5: Substitute Back \( u = x^{2} - 3 \)
Finally, replace \( u \) with the original substitution to express the answer in terms of \( x \):
\[
\frac{u^{3}}{3} + C = \frac{(x^{2} - 3)^{3}}{3} + C
\]
### Final Answer
\[
\int \left(x^{2} - 3\right)^{2} (2x) \, dx = \frac{(x^{2} - 3)^{3}}{3} + C
\]
**Summary of Substitution:**
\[
u = x^{2} - 3
\]
\[
du = 2x \, dx
\]
And the evaluated integral is:
\[
\frac{(x^{2} - 3)^{3}}{3} + C
\]
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Beyond the Answer
To change the integrand to the form \( u^{2} d u \), we can let \( u = x^{2} - 3 \). Then, calculating the differential \( d u \) gives us \( d u = (2x) d x \), which matches perfectly with the \( 2x d x \) present in your integral. Now, rewriting the integral in terms of \( u \), we have: \[ \int (u)^{2} d u \] To evaluate this integral, we use the power rule: \[ \frac{u^3}{3} + C \] Substituting back the expression \( u = x^2 - 3 \), the final answer is: \[ \frac{(x^2 - 3)^3}{3} + C \]
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium